Geochemical Characterization of Groundwater in the Confined and Unconfined Aquifers of the Northern Italy - Cristina Orecchia; Beatrice M. S. Giambastiani; Nicolas Greggio; Bruno Campo; Enrico Dinelli (Applied Sciences, 2022)
Having an accurate and easily accessible geochemical database is crucial for a correct groundwater management. Here, for the first time in Italy, chemico-physical data of groundwater collected by different Environmental Protection Agencies during the 2018 were integrated into a single database to assess the geochemical status of a wide and complex aquifer system. Data were assembled, reformatted, corrected, homogenized, and then grouped according to the aquifer type (phreatic, semi-confined, and confined) and the sampling seasons. A total of 3671 validated samples were classified into hydrochemical facies; inorganic N compounds and trace elements were also evaluated. The water were classified mainly as Ca-HCO3 and Ca-Mg-HCO3 (90%); locally, Na-HCO3, Mg-HCO3, Ca-SO4, Na-Cl, and Ca-Cl types were detected. In the phreatic aquifers, NO3 contamination and high concentrations of Na+, K+, and NH4+ were found and linked to anthropogenic sources, such as agricultural and livestock activities. Along the Adriatic coast, Na-Cl water confirmed saltwater intrusion phenomena. Landward, evaporitic rocks dissolution, and the upconing of relict marine water explained high EC, Na+, K+, Cl−, and SO42− concentrations. The dissolution of Fe-Mn oxide-hydroxides coupled with organic carbon oxidation under reducing environment justified high NH4+, Fe, Mn, and As recorded in the semi-confined and confined aquifers.